All Questions Topic List
Limits Questions
Previous in All Question Next in All Question
Previous in Limits Next in Limits
Question Number 184891 by mathlove last updated on 13/Jan/23
limx→πx−πsinx=?
Answered by Mathspace last updated on 13/Jan/23
chang.x−π=tgivelimx→πx−πsinx=limt→0tsin(π+t)=−limt→0tsint=−1
Answered by alephzero last updated on 13/Jan/23
limx→πx−πsinx=limx→π1cosx=1−1=−1
Answered by TUN last updated on 14/Jan/23
=limx→π−(π−x)sin(π−x)=−limx→ππ−xsin(π−x)=−1
Terms of Service
Privacy Policy
Contact: info@tinkutara.com